Enhanced PCO prevention of drug eluting IOLs via endocytosis and autophagy effects of a PAMAM dendrimer. Issue 3 (18th December 2020) - Qin, Chen; Liu, Sihao; Wen, Shimin; Han, Yuemei; Chen, Siqi; Qie, Jiqiao; Chen, Hao; Lin, Quankui
Abstract : Enhanced posterior capsular opacification prevention of drug eluting intraocular lens via the endocytosis and autophagy effects of a PAMAM dendrimer. Abstract : Drug-loaded intraocular lenses (IOLs) have received considerable attention in treating complications that arise after cataract surgery, especially posterior capsular opacification (PCO). However, for a better therapeutic effect, the drug concentration in IOLs usually needs to be increased. Herein, we developed multilayer (doxorubicin (DOX)@polyaminoamide (PAMAM) (D@P)/heparin sodium (HEP))5 modified IOLs, which efficiently enhance the inhibitory effect on PCO using the enhanced autophagy effect of a cationic PAMAM. The chemotherapeutic drug DOX was encapsulated in PAMAM to formulate cationic DOX@PAMAM nanoparticles. Subsequently, negatively charged HEP and D@P nanoparticles (NPs) were assembled on the aminated artificial IOL surface using the layer-by-layer (LBL) assembly technique. The (D@P/HEP)5 IOLs were implanted into rabbit eyes to evaluate the prevention of PCO. In vitro and in vivo research studies showed that the D@P NPs exhibited enhanced cellular uptake owing to the cell-penetrating cationic characteristics, while demonstrating enhanced autophagy. D@P NPs are more effective at the same DOX concentration when compared to free DOX. Multilayer-modified (D@P/HEP)5 IOLs can efficiently inhibit PCO after cataract surgery. This study provides a strategy for improving the therapeutic effect of antiproliferative drug DOX by using a cationic dendrimer, which, in turn, increases the level of autophagy of cells. These LBL-based multilayer IOLs have broad application prospects in the treatment of complications after cataract surgery.